Attitudes of Micro, Small and Medium Size Entrepreneurs on Nepalese Tax System (Patan Prospective Journal, 2025)
This study investigates how Nepalese micro, small, and medium-sized business (MSME) owners feel about the tax structure in their nation. Tax knowledge and awareness, perceived fairness of the tax system, tax process complexity, trust in the government and tax authorities, and perceived utility of tax income are all evaluated, as is their impact on attitudes toward tax compliance. Using convenience sampling and a structured questionnaire, information was gathered from 201 MSME owners in Chitwan. While correlation and regression analyses were used to look at relationships and test hypotheses, descriptive statistics provided a summary of the respondents' opinions. The results show that MSME owners have a favorable view toward the tax system due to their moderate to high levels of tax knowledge and awareness. Moderately fair tax rates, penalties, and equity were perceived, however this raised questions about uneven application and unfair treatment. Entrepreneurs' perceptions of the complexity of tax procedures were varied; while they found some processes manageable, they frequently needed outside help. Positive tax views were moderately impacted by perceived utility of tax revenue and trust in government and tax authorities, highlighting the need of transparency and obvious public benefits in encouraging compliance. Complexity was not a significant predictor of attitudes toward the tax system, according to regression results, but tax knowledge, perceived justice, trust in authorities, and perceived use of tax income all had a significant impact. To increase compliance among MSMEs in Nepal, our findings point to the necessity of focused tax education, enhanced equity and openness in tax administration, and streamlined tax procedures. Based on self-reported data and restricted to urban MSMEs, the study offers guidelines for future research that could incorporate longitudinal methods and rural locations.